Exploring Contemporary Thoughts on the Use of Environmental Enrichment Programs in 'No-Kill' Animal Shelters - Castillo, Roberto (Tufts Archival Research Center, 2019)
This research project seeks to explore the current thoughts surrounding the use of environmental enrichment programs within no-kill shelters in Northern Illinois. This project centers on discussions with workers pertaining to the practicalities of implementing environmental enrichment programs.; Thesis submitted for the MS in Animals and Public Policy degree.